Evolutionary perspectives on juvenile homicide offending - Meehan, Madeleine K. (The Routledge international handbook of juvenile homicide, 2024)
Evolutionary psychology applies the theoretical framework of evolution by natural selection to the study of psychology. Evolution by natural selection is a well-established theory of the nature of life but remains underappreciated in the psychological, behavioral, and social sciences. Evolutionary psychology examines and explains behaviors such as homicide at a distinct distal level, recognizing that humans are complex evolved systems exhibiting traits shaped by recurrent adaptive problems over evolutionary history. Just as the eye is an adaptation resulting from the non-random differential replication of genes, evolved psychological mechanisms are universal functional structures sensitive to environmental input and exist because they solved ancestral problems related to survival and reproduction. Adolescent and young adult violence and homicide are recurrent features of human evolutionary history and, therefore, evolved psychological mechanisms are relevant to understanding the prevalence and characteristics of juvenile homicide. An evolutionary perspective can provide new insights into juvenile homicide insofar as it encourages consideration of the ages of offenders, the relationships between victims and offenders, sex differences in perpetration and victimization, and other demographic characteristics of juvenile offenders.